The 100 dollar startup : reinvent the way you make a living, do what you love, and create a new future - Guillebeau, Chris, ....- (New York : Random House Usa, 2012)
In The $100 Startup, Chris Guillebeau shows you how to lead of life of adventure, meaning and purpose – and earn a good living. Still in his early thirties, Chris is on the verge of completing a tour of every country on earth – he's already visited more than 175 nations – and yet he's never held a "real job" or earned a regular paycheck. Rather, he has a special genius for turning ideas into income, and he uses what he earns both to support his life of adventure and to give back. There are many others like Chris – those who've found ways to opt out of traditional employment and create the time and income to pursue what they find meaningful. Sometimes, achieving that perfect blend of passion and income doesn't depend on shelving what you currently do. You can start small with your venture, committing little time or money, and wait to take the real plunge when you're sure it's successful. In preparing to write this book, Chris identified 1,500 individuals who have built businesses earning $50,000 or more from a modest investment (in many cases, $100 or less), and from that group he's chosen to focus on the 50 most intriguing case studies. In nearly all cases, people with no special skills discovered aspects of their personal passions that could be monetized, and were able to restructure their lives in ways that gave them greater freedom and fulfillment.